2023
DOI: 10.1111/nyas.14963
|View full text |Cite
|
Sign up to set email alerts
|

Polymeric carbon nitride as a platform for photoelectrochemical water‐splitting cells

Abstract: Polymeric carbon nitride (CN) materials are promising low-cost photocatalysts that exhibit a combination of chemical and physical properties suitable for converting light into redox activity on their surface. In this perspective, we describe our experience with this family of materials as light absorbers that serve as an anode in photoelectrochemical cells toward water-splitting. We describe some of the CN deposition techniques and procedures established in our lab. The knowledge gained from powderbased photoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 46 publications
(125 reference statements)
0
4
0
Order By: Relevance
“…The assessment of the efficiency of separation of electron–hole (e – –h + ) pairs, generated following photoexcitation, within the prepared materials, was conducted through the resultant photocurrents within a conventional photoelectrochemical cell (PEC) designed for water splitting Figure c reveals that DCDBA5 manifests the most notable photocurrent, attaining a value of ca.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The assessment of the efficiency of separation of electron–hole (e – –h + ) pairs, generated following photoexcitation, within the prepared materials, was conducted through the resultant photocurrents within a conventional photoelectrochemical cell (PEC) designed for water splitting Figure c reveals that DCDBA5 manifests the most notable photocurrent, attaining a value of ca.…”
Section: Resultsmentioning
confidence: 99%
“…Crystalline carbon nitride materials (CNs), such as poly­(heptazine imides) (PHI) and poly­(triazine imide) (PTI), have emerged as highly active photocatalysts for various reactions, including water splitting, CO 2 reduction, hydrogen peroxide synthesis, and organic transformation reactions. Their high activity compared to that of traditional CNs , is due to better light-harvesting properties, high specific surface area, suppressed recombination under illumination, and better charge mobility. , The synthesis of CNs with high crystallinity is typically achieved using molten salts as the reaction medium . The final composition and structure are usually determined by how the salt ions are stabilized at the high temperatures where the CN formation reaction takes place.…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, progress in the different deposition techniques developed in the state of the art to create CN layers has been reported in review articles, to which we would like to refer the reader. [8,123,124] Because the solubility of CN is poor in most solvents, owing to strong Van der Waals interactions, the films prepared by conventional methods are inhomogeneous and weakly attached to the employed transparent electrodes. Our group and others observed that the pyrolysis of supramolecular films prepared with C/N-based monomers allows the construction of CN-based films in robust contact with the electrode.…”
Section: Enhanced Charge Transfer In Photoelectric Devicesmentioning
confidence: 99%
“…The stability of PCN on electrodes also needs to be improved. [141] None of the reported energy-storing devices for photocathodic protection can shift the OCP of steel down < −0.8 V versus Ag/AgCl in the dark, but different examples of heterojunctions with TiO 2 can meet that requirement under illumination. [100,104,112,118,122,124,125,127,135] For these materials, charge accumulation might still be relevant to prolong the lifetime of steel, where corrosion could be reasonably prevented during the day and sufficiently slowed down at night.…”
Section: Photocathodic Protection For Anti-corrosionmentioning
confidence: 99%